Does paycheck frequency matter? Evidence from micro data - Baugh, Brian; Correia, Filipe (Journal of Financial Economics, 2022)
Using a unique dataset from an account aggregator, we analyze cross-sectional differences and within-household time-series variation in paycheck frequency. We find that higher paycheck frequency results in less credit card borrowing, less consumption, but more instances of financial distress — even when the change in paycheck frequency is employer-initiated. We find that pay frequency strongly determines within-month time patterns of financial distress. Our theoretical model reconciles these empirical results — higher paycheck frequency increases consumers’ willingness to allocate to illiquid savings vehicles, leading to a reduction in both consumption and within-paycycle borrowing.